Potential of Adhocracy Culture in Shaping Character Development and Social Quality of Islamic Students - Muhammad Munif; Ahmad Faidul Mannan (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study explores the potential of adhocracy culture in strengthening character development and social quality among Islamic boarding school (pesantren) students. Contemporary pesantren face increasing challenges in responding to rapid social change, globalization, and the need to balance spiritual formation with social adaptability. Many pesantren still rely on hierarchical organizational cultures that limit innovation, participation, and students’ social agency. This research adopts a qualitative case study approach to examine how an adhocracy-based organizational culture can address these challenges. Data were collected through in-depth interviews, participatory observation, and document analysis involving mentors, pesantren administrators, students, and partner institutions. The findings reveal three main contributions. First, spiritual leadership plays a crucial role in providing ethical direction and moral boundaries for innovation, ensuring that flexibility and creativity remain aligned with Islamic values. Second, the implementation of adhocracy culture enhances students’ independence, responsibility, and social awareness through participatory decision-making, collaborative projects, and community-based activities. Third, the integration of ethnopedagogical approaches allows innovation to be rooted in local wisdom, strengthening students’ cultural identity and facilitating deeper internalization of moral and social values. Overall, the study concludes that adhocracy culture, when combined with spiritual leadership and ethnopedagogy, offers an effective and contextually relevant model for developing adaptive, creative, and socially responsible santri. This research contributes to the limited literature on organizational culture in Islamic education and provides practical implications for pesantren seeking to strengthen character education in a changing social context.